Breast internal dose measurements in a physical thoracic phantom - Silva, Sabrina Donato da; Oliveira, Márcio Alves de; Castro, André Lima de Souza; Dias, Humberto Galvão; Nogueira, Luciana Batista; Campos, Tarcisio Passos Ribeiro de (Scientia Plena, 2017)
Radiotherapy is a cancer treatment intended to deposit the entire prescribed dose homogeneously into a target volume in order to eliminate the tumor and to spare the surrounding healthy tissues. This paper aimed to provide a dosimetric comparison between the treatment planning system (TPS) ECLIPSE from Varian Medical Systems and the internal dosimetric measurements in a breast phantom. The methodology consisted in performing a 3D conformal radiotherapy planning with two tangential opposite parallel fields applied to the synthetic breast in a thoracic phantom. The irradiation was reproduced in the Varian Linear accelerator, model SL – 20 Precise, 6 MV energy. EBT2 Radiochromic films, placed into the glandular equivalent tissue of the breast, were used to measure the spatial dose distribution. The absorbed dose was compared to those values predicted by the treatment planning system; besides, the dosimetric uncertainties were analyzed. The modal absorbed dose was in agreement with the prescribed value of 180 cGy, although few high dose points between 180 and 220 cGy were detected. The findings suggested a non-uniform dose distribution in the glandular tissue of the synthetic breast, similar to those found in the TPS, associated with the irregular anatomic breast shape and presence of inhomogeneities next to the thoracic wall generated by the low lung density.